Use of Marijuana Edibles by Adolescents in California - Friese, Bettina (J Prim Prev, 2017)
We explored how adolescent marijuana edible users differ in regards to marijuana use and related beliefs from marijuana users who do not use edibles. We analyzed California Healthy Kids Survey data collected in one Northern California school district with a racially and ethnically diverse student population. Survey respondents were youth in grades 9 – 12. Overall, 33% of respondents reported having used marijuana in their lifetime, and 50% of lifetime marijuana users reported using marijuana in the past 30 days. Seventy-two percent of lifetime marijuana users and 82% of past month marijuana users reported having used edibles in their lifetime. Comparing marijuana users who have never used edibles to those users who have, we found that edible users reported using marijuana more frequently in their lifetime. Edible users were also more likely to have used marijuana in the past 30 days, more frequently in the past 30 days, more likely on school property and more frequently on school property. Edible users and non-users differed in their perceptions of risk; edible users were less likely to agree that edible use is very risky. Edible users also reported a younger age of first marijuana use and more attempts to stop using marijuana than non-edible users. Multi-level regression analyses indicate that prevalence of edible use among marijuana users was related to perceived risk of edible use. Perceived risk of edible use among marijuana users was higher among marijuana users who do not use edibles, females, and those youth who perceive school rules to be clear. The findings indicate that prevalence of edible use is high among marijuana users, especially frequent users.